Aid when ‘there is nothing left to offer’: Experiences of palliative care and palliative care needs in humanitarian crises - Lisa Schwartz; Elysée Nouvet; Sonya de Laat; Rachel Yantzi; Olive Wahoush; Wejdan A. Khater; Emmanuel Musoni Rwililiza; Ibraheem Abu-Siam; Gautham Krishnaraj; Takhliq Amir; Kevin Bezanson; Corinne Schuster Wallace; et al. (PLOS Global Public Health, 2023)
Access to palliative care, and more specifically the alleviation of avoidable physical and psychosocial suffering is increasingly recognized as a necessary component of humanitarian response. Palliative approaches to care can meet the needs of patients for whom curative treatment may not be the aim, not just at the very end of life but alleviation of suffering more broadly. In the past several years many organizations and sectoral initiatives have taken steps to develop guidance and policies to support integration of palliative care. However, it is still regarded by many as unfeasible or aspirational in crisis contexts; particularly where care for persons with life threatening conditions or injuries is logistically, legally, and ethically challenging. This article presents a synthesis of findings from five qualitative sub-studies within a research program on palliative care provision in humanitarian crises that sought to better understand the ethical and practical dimensions of humanitarian organizations integrating palliative care into emergency responses. Our multi-disciplinary, multi-national team held 98 in-depth semi-structured interviews with people with experiences in natural disasters, refugee camps in Rwanda and Jordan, and in Ebola Treatment Centers in Guinea. Participants included patients, family members, health care workers, and other staff of humanitarian agencies. We identified four themes from descriptions of the struggles and successes of applying palliative care in humanitarian settings: justification and integration of palliative care into humanitarian response, contextualizing palliative care approaches to crisis settings, the importance of being attentive to the ‘situatedness of dying’, and the need for retaining a holistic approach to care. We discuss these findings in relation to the ideals embraced in palliative care and corresponding humanitarian values, concluding that palliative care in humanitarian response is essential for responding to avoidable pain and suffering in humanitarian settings.